2004
DOI: 10.1046/j.0902-4441.2003.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin has an anti‐myeloma effect – a hypothesis based on a clinical observation supported by animal studies

Abstract: Recombinant human erythropoietin (rHuEpo) was introduced into clinical practice more than a decade ago, and has been found to be effective in the treatment of several types of anemia, including anemia of end-stage renal failure and cancer-related anemia. No study has suggested that Epo might have an effect on the biology of the disease, nor any survival advantage to cancer patients treated with Epo for anemia has been reported. Here we report six patients with advanced multiple myeloma (MM) with very poor prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
35
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 59 publications
(59 reference statements)
3
35
0
1
Order By: Relevance
“…Our previous studies have demonstrated EPO-associated anti-neoplastic activities, which were related to EPO's action on the immune system (Mittelman et al, 2004;PrutchiSagiv et al, 2006). These studies were led by the observation that multiple myeloma (MM) patients treated with rHuEPO for their anemia, exhibited prolonged survival and improved quality of life (Baz et al, 2007;Mittelman et al, 1997;Mittelman et al, 2004).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our previous studies have demonstrated EPO-associated anti-neoplastic activities, which were related to EPO's action on the immune system (Mittelman et al, 2004;PrutchiSagiv et al, 2006). These studies were led by the observation that multiple myeloma (MM) patients treated with rHuEPO for their anemia, exhibited prolonged survival and improved quality of life (Baz et al, 2007;Mittelman et al, 1997;Mittelman et al, 2004).…”
Section: Introductionmentioning
confidence: 94%
“…These studies were led by the observation that multiple myeloma (MM) patients treated with rHuEPO for their anemia, exhibited prolonged survival and improved quality of life (Baz et al, 2007;Mittelman et al, 1997;Mittelman et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from these authors indicated that EPO may prolong survival in MM patients [8], and these results have been supported by other scientists [9]. The effect of EPO on MM was also reproduced in murine models, where EPO promotes the development of an effective and long-lasting anti-tumor specific immune response mediated via activated CD8 + T cells [10].…”
mentioning
confidence: 68%
“…In addition, epoetin alfa treatment, either in the absence of chemotherapy or concomitant with mild chemotherapy for a short duration, produced an antimyeloma effect and prolonged survival in a small study of patients with MM (n = 5) who had advanced disease and an expected survival of less than 6 months [111]. Despite a poor prognosis, patients survived an additional 42-82 months after initiation of epoetin alfa therapy [111]. These findings are consistent with data from a murine model of MM, where tumor regression believed to be mediated via activated CD8 + T cells occurred in 50% of mice inoculated with MM cells [112].…”
Section: Epo: Functions Beyond Erythropoiesismentioning
confidence: 99%
“…Epoetin alfa alone had no effect on growth of a lung carcinoma xenograft; however, in synergy with cisplatin, it induced a fivefold reduction in tumor mass [110]. In addition, epoetin alfa treatment, either in the absence of chemotherapy or concomitant with mild chemotherapy for a short duration, produced an antimyeloma effect and prolonged survival in a small study of patients with MM (n = 5) who had advanced disease and an expected survival of less than 6 months [111]. Despite a poor prognosis, patients survived an additional 42-82 months after initiation of epoetin alfa therapy [111].…”
Section: Epo: Functions Beyond Erythropoiesismentioning
confidence: 99%